Uncovering Barriers to Rural Development to Empower Communities in Indonesia - Novitasari, Wulan; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
This research analyzes the role of the Village Community Empowerment Institution (LPMD) in the development of Watesnegoro village, Ngoro sub-district, Mojokerto district. Using a descriptive qualitative approach, data were collected from the village head, LPMD head, village secretary, treasurer, and planning officer through observation, interviews, and documentation. The study finds that while LPMD efforts in socialization, training, and community skill improvement are positive, overall effectiveness is limited by low community participation and inadequate human resources. Enhancing community involvement and human resource quality is essential for the success of LPMD programs and village economic development. Highlights: LPMD's Impact Assessment: Vital for Watesnegoro Village Development. Limited Engagement: Hinders LPMD Programs and Economic Growth. Skill Enhancement: Key to Effective LPMD and Community Empowerment. Keywords: LPMD, Village Development, Community Empowerment, Mojokerto District, Qualitative Analysis